Impact of World Thrombosis Day campaign. Issue 1 (July 2017) - Wendelboe, Aaron M.; St. Germain, Louise; Krolak, Barbara; Reiser, Thomas; Raskob, Gary; ,
Abstract: Thrombosis is an underlying cause of one in four deaths globally. The International Society on Thrombosis and Haemostasis established the inaugural World Thrombosis Day on October 13, 2014. The World Thrombosis Day campaign aims to 1) highlight the disease burden from thrombosis, 2) increase public awareness of the risks, signs, and symptoms of thromboembolic conditions, 3) empower individuals to discuss their thrombosis risk with their healthcare provider, 4) galvanize organizations across the globe, and 5) advocate for "systems of care" to prevent, diagnose, and treat venous thromboembolism and atrial fibrillation. Public health messages include: "know the risks, signs, and symptoms of blood clots, " "potentially fatal blood clots in the veins can be prevented, " "atrial fibrillation can be diagnosed by a doctor feeling one's pulse, " and "effective strategies for stroke prevention in patients with atrial fibrillation are available." To demonstrate the public health impact of the World Thrombosis Day campaign, we measured campaign reach, size and breadth of our partner network, as well as traditional and digital media impressions. The campaign reached an estimated ≥2.3 billion people globally in 2016. As part of the World Thrombosis Day campaign, approximately 8, 200 activities were held globally and our partner network expanded to ≥675 partners across 80 countries in 2016. Social media metrics reached 170 million impressions and traditional media reached 1.9 billion impressions. We appreciate and thank our partners for their contributions and encourage others to support this campaign to reduce thrombosis‐related morbidity and mortality worldwide.